Penguatan Transparansi Dana BOS sebagai Praktik Pendidikan Kewarganegaraan di SD Eka Tjipta 01 Telen - Rahmawati, Ayu; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Civics education is not merely oriented toward normative knowledge of citizens’ rights and obligations, but also functions to instill moral values, responsibility, honesty, and public awareness through concrete practices in school life. One institutional practice closely related to civic values is the management of School Operational Assistance (BOS) funds as public funds provided by the state. This study aims to analyze the strengthening of transparency in BOS fund management as a practice of Civics Education and moral education at SD Eka Tjipta 01 Telen. This research employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews with the principal, BOS treasurer, and teachers, as well as documentation studies of the School Activity and Budget Plan (RKAS) and BOS financial reports. Data analysis was conducted using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that BOS fund management at SD Eka Tjipta 01 Telen has been implemented in accordance with applicable regulations and demonstrates a commitment to building public accountability. The transparency practices applied contribute to fostering honesty, responsibility, and openness as core values of civic education. However, the participation of school stakeholders in interpreting BOS fund management as a learning medium for Civics Education still requires further strengthening to ensure optimal internalization of civic values.